Drug Control and Development: A Blind Spot - Julia Buxton (Revue Internationale de Politique de Développement)
Development questions have been central to international drug policy since the first tentative steps towards a global control regime over a century ago. The strategy that was devised to limit the cultivation of mind- and mood-altering plants imposed a disproportionate cost on cultivating territories in the global South. This burden intensified in the post-war period and as the 1961 Single Convention on Narcotic Drugs and United States ‘war on drugs’ in the 1970s institutionalised ‘narcotics’ as a security issue and a law enforcement concern. Despite criminalisation and coercive state eradication efforts, illicit narcotic plant cultivation (opium poppy, coca) has persisted, reaching record highs after 2015. Recent decades have seen improved understanding of development deficits as the driver of sustained illicit cultivation. However, high-level efforts to promote inter-agency and thematic linkages between drug strategy and global development goals have seen the reinvention of orthodox approaches to both drug control and poverty reduction. Neither has a record of sustainable success or of raising concerns as to the counterproductive impacts of policy reproduction. In patching together new ideas within failing paradigms, alternative development is better understood as ‘policy bricolage’.